“Skin Shades” of Marriage: Viewers’ Perspectives on Controversial Skincare TV Advertisements in Malaysia - Mohamad, Hairul Azhar; Abd Rahman, Amir Lukman; Abdul Wahab, Nadiah Hanim; Abd Rashid, Muhammad Haziq; Md Zolkapli, Rasyiqah Batrisya (Asian Social Work Journal, 2024)
With the massive use of skincare products among Malaysians, advertisements for these products are becoming more targeted and personalised, but at the same time, they are also becoming more intrusive and misleading. Therefore, the present study aims to identify the controversial elements portrayed in these skincare TV advertisements and analyse whether these elements are deemed viable marketing strategies by the target audience. A questionnaire adapted from Lester’s Six Perspectives of Visual Communication was distributed to 140 skincare users. Results from the questionnaire revealed that most respondents perceived the approach used by the skincare companies in their advertisements sampled in this research to be highly controversial in terms of their different approaches. Male viewers showed their strong perception on the importance of controversial consideration to produce any skincare TV advertisements. This was based on their perceptions towards the same advertisements presented with the controversial idea that the shade of the skin would determine the stability of the marriage. However, a thorough review should be conducted on these controversial advertisements to ensure they do not violate the target audience’s moral beliefs. By having a specific guideline on the advertising code of conduct, it will ensure that the advertisements will be well-received by them despite the controversial approach. Future research can be done to focus on the different levels of consideration shown by viewers from the old and new generations for more informative findings on this style of advertisement.